Do politicians affect firm outcomes? Evidence from connections to the German Federal Parliament - André Diegmann; Laura Pohlan; Andrea Weber (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
We study how connections to German federal parliamentarians affect firm dynamics by constructing a novel dataset to measure connections between politicians and the universe of firms. To identify the causal effect of access to political power, we exploit (i) new appointments to the company leadership team and (ii) discontinuities around the marginal seat of party election lists. Our results reveal that connections lead to reductions in firm exits, gradual increases in employment growth without improvements in productivity. The economic effects are mediated by better credit ratings while access to subsidies or procurement contracts are documented to be of lower importance.
Keywords: O43; L25; D72; 330; Politicians; Firm Performance; Identification; Political Connections